Effect of Tenure, Audit Specialization, and KAP's Reputation on the Quality of Audit Mediated by Audit Committees - Atmojo, Rifqi Tri; Sukirman, Sukirman (Accounting Analysis Journal, 2019)
The purpose of doing research is to analyze the influence of tenure, specialty audit, Audit Firm's reputation on quality auditing, and third variable interaction of audit quality when moderated by audit committee. A number of manufacturing companies of 156 listed in IDX period 2011-2016 become the population this research. A number of 44 companies selected as samples by using purposive sampling technique. The Research used multiple regression analysis, while interaction variables tested with Moderated Regression Analysis (MRA) by using IBM SPSS version 21. The results of this study showed tenure have no effect to audit quality. There are positive and significant influence of audit specialization to audit quality. Meanwhile, reputation of audit firm and significant influential audit committee with a negative direction against quality of audit. The study also proved that audit Committee was able to moderate the relationship of audit specialization to audit quality as well as relationship of audit firm’s reputation of quality audit. However, the audit committee is not able to moderate relationship of tenure with audit quality. A summary of this research is role of audit committee is crucial in bridging audit firm and corporate relationships as well as maintaining quality of audit results.